An Ecological Comparison of Floristic Composition in Seasonal Semideciduous Forest in Southeast Brazil: Implications for Conservation - Sérgio de Faria Lopes; Ivan Schiavini; Ana Paula Oliveira; Vagner Santiago Vale (International Journal of Forestry Research)
We examined floristic patterns of ten seasonal semideciduous forest sites in southeastern Brazil and conducted a central sampling of one hectare for each site, where we took samples and identified all individual living trees with DBH (diameter at breast height, 1.30 m) ≥4.8 cm. Arboreal flora totaled 242 species, 163 genera, and 58 families. Fabaceae (38 species) and Myrtaceae (20 species) were families with the largest number of species. Only Copaifera langsdorffii and Hymenaea courbaril occurred at all sites. Multivariate analysis (detrended correspondence analysis and cluster analysis) using two-way indicator species analysis (TWINSPAN) indicated the formation of a group containing seven fragments in which Siparuna guianensis was the indicator species. This analysis revealed that similarities between studied fragments were due mainly to the successional stage of the community.